A Lingual Thyroid Associated With Congenital Profound Sensorineural Hearing Loss - Elmustafa, Osman M; Abdelkarim, Mohammed El M; Osman, Wail N (Gezira Journal of Health Sciences, 2012)
This is a case report of an extremely rare case of a lingual thyroid associated with profound bilateral congenital sensorineural hearing loss in a Sudanese girl. To our knowledge this association has not been previously reported. :الملخص هذا تقرير حالة نادرة الحدوث لغدة درقية لسانية مرتبطة مع صمم حسي عصبي ولادي وخيم ثنائي الجانب لدى فتاة سودانية. حسب علمنا هذا الإرتباط لم يسبق الإبلاغ عنه